Analisis Pengaruh Pertumbuhan Ekonomi Dan Indeks Pembangunan Manusia Terhadap Tingkat Pengangguran Di Sumatera Utara - Tumangger, Indah; Nurlina, Nurlina; Miswar, Miswar (STIE Jambatan Bulan, 2025)
This research aims to determine the influence of economic growth and the human development index on the unemployment rate in North Sumatra during 2010-2023. The data used in this research is secondary data obtained from the Central Statistics Agency of North Sumatra Province. The data obtained was then analyzed using the Eviews 10 application. The method used in the research was the multiple linear regression analysis method. The variables in this research include the unemployment rate as the dependent variable and economic growth and the human development index as the independent variables. The research results show that economic growth has a negative and significant effect on the unemployment rate in North Sumatra and the human development index also has a negative and significant effect on the unemployment rate in North Sumatra. Economic growth and the human development index have a significant effect on the unemployment rate in North Sumatra.